PENGEMBANGAN MEDIA POP-UP BOOK WARUNG MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SEKOLAH DASAR - Deshinta Fatikasari; Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of appropriate learning media in learning is very important to attract students' attention. However, in reality, the learning process in elementary schools is still dominated by the lecture method, which makes students passive recipients of information and hinders their development to be able to think critically and solve problems. This study aims to develop pop-up book learning media to improve problem solving for fifth grade students, to determine the validity of the pop-up book Warung Matemtika learning media for mathematics learning content on the material of hundreds of thousands of arithmetic operations for fifth grade elementary school students, to determine the effectiveness of the Po-Up Book Warung Matematika learning media to improve problem solving skills in fifth grade elementary school students, and to determine the practicality of the Pop-Up Book Warung Matematika learning media to improve problem solving skills in fifth grade elementary school students. This research with the type of Research and Development (R&D) uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) with the research subjects being fifth grade students of SD Negeri Butuh 01. Based on the results of the study, it was found that the results of the limited trial that had been carried out in Negeri Butuh 01 produced an average value in the pretest of 70.8 and after being treated with the Pop-Up Book Warung Matematika media, the average value in the final measurement was 82.3 with a difference in increase of 11.5 and the T-Test produced a data value that showed sig (2-tailed) of 0.001 so that the Sig.(2 tailed) value is 0.001 < 0.05, then it can be concluded with the hypothesis that the posttest results are higher than the pretest.